Combined use of graphical and statistical approaches for rainfall trend analysis in the Mae Klong River Basin, Thailand - Alamgir Khalil (Journal of Water and Climate Change, 2023)
The main purpose of this paper was to investigate the monthly, seasonal, and annual rainfall variability in the Mae Klong River Basin in Thailand using the Mann–Kendall (MK) test, Sen's slope method, Spearman's Rho (SR) test, and the innovative trend analysis (ITA) method. The monthly rainfall data of eight stations for the period 1971–2015 were used for trend analysis. Datasets with significant serial correlation were corrected by the trend-free pre-whitening (TFPW) approach for statistical methods. The MK test showed increasing rainfall trends for five out of eight stations in the dry season while 50% of stations indicated increasing trends in the wet season. On an annual scale, 75% of the stations exhibited increasing rainfall trends. The results of the SR test were in line with the MK test for seasonal and annual rainfall. The ITA method showed comparable findings with those of the statistical methods. For the entire basin, trend analysis found increasing rainfall on both seasonal and annual scales by all the tests. The findings of this study could benefit water supply and management, drought monitoring, agricultural production activities, and socioeconomic development in the Mae Klong River Basin in the future. HIGHLIGHTS Statistical methods and graphical methods for rainfall trends are compared.; Datasets with significant serial correlation were corrected by the trend-free pre-whitening (TFPW) approach for statistical methods.; The results of Spearman's Rho test were in line with the Mann–Kendall test for seasonal and annual rainfall.; The innovative trend analysis method showed comparable findings with those of the statistical methods.;